Graphene oxide/poly(vinyl imidazole) nanocomposite: an effective support for preparation of highly loaded heterogeneous copper catalyst. (15th June 2015) - Pourjavadi, Ali; Safaie, Niloofar; Hosseini, Seyed Hassan; Bennett, Craig
<x xml:space="preserve">Abstract</x> A heterogeneous polymeric catalyst was synthesized by immobilization of copper ions in a graphene oxide/poly(vinyl imidazole) nanocomposite. This catalyst has proven to be highly active in a practical protocol for click synthesis of 1, 2, 3‐triazole via one‐pot three‐component cycloaddition of halides, terminal alkynes and sodium azide. The reaction was carried out in water medium and good to excellent yields of products were obtained using only 1.0 mol% of catalyst. The catalyst can be readily recovered and reused eight times under the described reaction conditions without significant loss of activity. The reaction also proceeded well with only 0.002 mol% of catalyst, which shows the high activity of the resulting copper‐loaded nanocomposite. Copyright © 2015 John Wiley & Sons, Ltd.